Sizing of biomass and solar photovoltaic hybrid renewable energy system for tropical climate - Muhamad, Mohd Izhwan (2016)
Nowadays, the electricity utility provider has started to consider a green power generation due to rapid depletion of fossil fuel reserves as well as world climate change. Among potential green and renewable resources are solar, wind and biomass which are environmental friendly, less cost and sustainable energy alternatives. However, all these resources are not available all the time throughout the year which lead to wide research works on Hybrid Renewable Energy System (HRES) by combining multiple energy resources. In addition, energy generated from the HRES is proven to have better quality and more reliable to end users rather than a system with only a single resource. Malaysia is located in tropical region which receives solar energy from sunlight consistently throughout the year. Besides that, Malaysia is also rich with biomass resources. The prospect of biomass energy resource especially from the oil palm industry is bright as it has become major sustainable energy in Malaysia. The previous renewable energy system (RES) shows significant disadvantages such as reliability of supply, difficult to generate energy in large quantity, increasing cost of the diesel oil for diesel generator and CO2 emission. When the system combines a few resources, the energy generated will be flexible based on availability of the resources. Combining solar and biomass will be a unique work as firstly explored. However, without the dispatch strategy, the total cost of the system is much higher. Besides that, CO2 emission, total net present cost (TNPC) and cost of energy (COE) can be reduced by the HRES as compared to the RES. Therefore, this research works is aimed to develop the best configuration of HRES mainly combining biomass and solar as renewable energy resources, in terms of sizing and strategy of operational aspect, with minimum amount of excess energy and CO2 emission. The pilot area, where the system was planned to be considered for the optimization work is the Halal Products Research Institute (IPPH), located in Universiti Putra Malaysia. The IPPH’s building is operating with a lot of research high-end equipment which consumes a very high power. The research started with development of HRES by considering sizing and strategy of operational aspect with biomass and solar resources either as standalone or grid-connected systems. The proposed HRES was evaluated by considering TNPC, COE, CO2 emissions and excess energy. The evaluation of the energy potential from solar and biomass resources in Malaysia is presented. The best configuration of hybrid renewable energy system in terms of sizing and operational strategy by combining solar and biomass resources for stand-alone and grid-connected, have been modeled. The results presented for both HRESs are based on adjustment to capacity (or size) and price of components. The HRES with possible dispatch strategy has been determined to produce energy to meet the load demand. The performance of the stand-alone and grid-connected HRES has also been compared in terms of TNPC and COE. The HOMER is found to be widely used. Many researchers highlighted the usefulness of the HOMER as compared to other tools. The analysis can easily be done to evaluate the feasible and optimal configuration of the system. From the review, HOMER is chosen to be used to perform simulation and analysis in this research. Finally, it shows that the stand-alone configuration of HRES with load following dispatch strategy shows the lowest of producing CO2 emissions and excess energy.